Digital Therapeutics in Perspective: From Regulatory Challenges to Post-Marketing Surveillance - Crisafulli, Salvatore; Santoro, Eugenio; Recchia, Giuseppe; Trifirò, Gianluca (Frontiers in Drug Safety and Regulation, 2022)
Digital therapeutics (DTx) are innovative therapeutic interventions, in which the therapeutic activity is carried out by algorithms and software. They represent a new opportunity especially for the treatment of chronic pathologies associated with dysfunctional lifestyles and behaviors, where conventional drug therapy is not fully effective. DTx are highly customizable therapeutic tools, allowing a better involvement of the patient in the management of the disease. To date, the clinical use of DTx in Europe is still generally limited. One of the main issues related to DTx is the general lack of education of healthcare professionals in this sector that leads to a knowledge gap between data scientists, and physicians, who should identify all those clinical needs that could be better addressed through the use of DTx. From a regulatory perspective, DTx are classified as Medical Devices. However, their research and development process is similar to that of conventional drugs, since they are tested in clinical trials and their approval refers to specific therapeutic indications. For this reason, precise criteria for marketing approval, for the health technology assessment and for the reimbursement of these therapies need to be defined. Moreover, as for conventional drugs, it is also fundamental to conduct post-marketing studies on DTx, aiming at re-evaluating the benefit-risk profile and collecting information related to large-scale use in real world setting. The aim of this review is to describe the main challenges for DTx development, regulation and widespread clinical use.